Personal attitudes towards smoking in a national sample of Aboriginal and Torres Strait Islander smokers and recent quitters. (1st June 2015) - Nicholson, Anna K; Borland, Ron; Bennet, Pele T; van der Sterren, Anke E; Stevens, Matthew; Thomas, David P
Abstract: Objectives: To describe attitudes towards smoking in a national sample of Aboriginal and Torres Strait Islander smokers and recent quitters and assess how they are associated with quitting, and to compare these attitudes with those of smokers in the general Australian population. Design, setting and participants: The Talking About The Smokes project used a quota sampling design to recruit participants from communities served by 34 Aboriginal community‐controlled health services and one community in the Torres Strait. We surveyed 1392 daily smokers, 251 non‐daily smokers and 78 recent quitters from April 2012 to October 2013. Main outcome measures: Personal attitudes towards smoking and quitting, wanting to quit, and attempting to quit in the past year. Results: Aboriginal and Torres Strait Islander daily smokers were less likely than daily smokers in the general Australian population to report enjoying smoking (65% v 81%) and more likely to disagree that smoking is an important part of their life (49% v 38%); other attitudes were similar between the two groups. In the Aboriginal and Torres Strait Islander sample, non‐daily smokers generally held less positive attitudes towards smoking compared with daily smokers, and ex‐smokers who had quit within the past year reported positive views about quitting. Among the daily smokers, 78% reported regretting starting to smoke and 81% reported spending too much money on cigarettes, both of which were positively associated with wanting and attempting to quit; 32% perceived smoking to be an important part of their life, which was negatively associated with both quit outcomes; and 83% agreed that smoking calms them down when stressed, which was not associated with the quitting outcomes. Conclusions: Aboriginal and Torres Strait Islander smokers were less likely than those in the general population to report positive reasons to smoke and held similar views about the negative aspects, suggesting that factors other than personal attitudes may be responsible for the high continuing smoking rate in this population.